(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article briefly presents the importance of introducing a competency-based approach to the open source system. The methods, methods, techniques used in the formation of general competencies in the disciplines of the professional cycle are briefly described.